Preparation and Characterization of Starch Particles for Use in Pickering Emulsions. Issue 2 (23rd November 2015) - Saari, Hisfazilah; Heravifar, Katayoun; Rayner, Marilyn; Wahlgren, Marie; Sjöö, Malin
Abstract : Particle‐stabilized emulsions, called Pickering emulsions, can be produced by using starch particles. In this work we studied how the properties of the starch particles affect the droplet size and creaming of such emulsions. In the study, various sizes of starch particles were generated by two different methods and used to stabilize Pickering emulsions. Sedimentation according to Stokes' law was used to separate small and large starch granules. Acid hydrolysis was another method used to obtain smaller particles. All samples were modified with octenyl succinic anhydride (OSA) to increase their hydrophobicity with a level of OSA substitution between 1.8 and 3.1%. The size of starch particles was the main factor influencing emulsion droplet sizes. Furthermore, the droplet size decreased as the starch concentration increased. Using small starch particles with sizes <10 μm produced stable emulsions with smaller droplet size compared with larger sizes of starch particles, >10 μm. When subjected to acid hydrolysis, smaller starch particles were generally obtained, which could subsequently create smaller emulsion droplets. The emulsion index increased for the acid‐hydrolyzed starch owing to the size reduction of starch particles. The shape of the starch seemed to have a minor impact on the droplet size and the creaming of Pickering emulsions.